Business Performance and Organizational Sustainability in the Muslim Fashion Industry through Religious-Centric Product Strategies - Ramadhani, Noor Laila; Nurcahyo, Satria Avianda; Isnawati, Setya Indah; Ilyasa Bin Muhammad Faiq (Journal of Digital Marketing and Halal Industry, 2025)
This research aims to  explores the impact of religious-centric product strategy, operational sustainability, and product quality on business performance in the Muslim fashion industry in Central Java. Using a quantitative approach with SEM PLS analysis, data was collected from 285 Muslim fashion outlets. The study aimed to test four hypotheses and two mediation tests to understand the relationships among the constructs. The results indicate that religious-centric product strategy positively influences operational sustainability and product quality, which in turn significantly affects business performance. Furthermore, operational sustainability and product quality were found to have significant mediation effects on the relationship between religious-centric product strategy and business performance. However, one hypothesis—regarding the direct relationship between religious-centric product strategy and business performance—was found to be non-significant. This suggests that while religious-centric strategies are crucial for enhancing operational sustainability and product quality, their direct effect on business performance is less pronounced. Overall, the findings highlight the importance of integrating religious values into business strategies for improving sustainability and quality, which, in turn, drive business performance in the Muslim fashion sector. This study contributes to the understanding of how religious-based strategies can influence business outcomes and provides practical implications for businesses aiming to enhance their competitiveness in the market. Keywords: Business Performance, Religious Centric Product Strategies, Organizational Sustainability, Maqashid Syariah